Peroxisomal Targeting as a Sensitive Tool to Detect Protein-Small RNA Interactions through in Vivo Piggybacking - Incarbone, Marco; Ritzenthaler, Christophe; Dunoyer, Patrice (Frontiers in Plant Science, 2018)
Peroxisomes are organelles that play key roles in eukaryotic metabolism. Their protein complement is entirely imported from the cytoplasm thanks to a unique pathway that is able to translocate folded proteins and protein complexes across the peroxisomal membrane. The import of molecules bound to a protein targeted to peroxisomes is an active process known as ‘piggybacking’ and we have recently shown that P15, a virus-encoded protein possessing a peroxisomal targeting sequence, is able to piggyback siRNAs into peroxisomes. Here, we extend this observation by analyzing the small RNA repertoire found in peroxisomes of P15-expressing plants. A direct comparison with the P15-associated small RNA retrieved during immunoprecipitation (IP) experiments, revealed that in vivo piggybacking coupled to peroxisome isolation could be a more sensitive means to determine the various small RNA species bound by a given protein. This increased sensitivity of peroxisome isolation as opposed to IP experiments was also striking when we analyzed the small RNA population bound by the Tomato bushy stunt virus-encoded P19, one of the best characterized viral suppressor of RNA silencing (VSR), artificially targeted to peroxisomes. These results support that peroxisomal targeting should be considered as a novel/alternative experimental approach to assess in vivo interactions that allows detection of labile binding events. The advantages and limitations of this approach are discussed.